2014
DOI: 10.3141/2444-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waste Engine Oil Residue on Quality and Durability of SHRP Materials Reference Library Binders

Abstract: This paper discusses the effects of widely used waste engine oil (WEO) residue on asphalt binder properties. Five SHRP Materials Reference Library binders and one commercial material from Ontario, Canada, were modified with 15% WEO. Materials were aged according to a standard rolling thin film oven protocol followed by 20 and 40 h of pressure aging vessel (PAV). Binder quality was determined according to AASHTO specification M 320 as well as dynamic shear characterization. Durability was assessed after additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Waste engine oil residue stands out as a modifier since it is a high-volume byproduct from the recycling of used oils without much value for further refining. Engine oil typically is formulated with saturated, high molecular weight alkanes with few branches, possessing low volatility, good high-temperature oxidative stability, and low viscosity at cold winter temperatures (2). Nuclear magnetic resonance spectroscopy shows that waste engine oil residue is entirely saturated and is therefore better described as consisting of equal parts saturates and polar (oxidized) saturates rather than aromatics.…”
Section: Descriptions Of the Materials Used Followmentioning
confidence: 99%
See 2 more Smart Citations
“…Waste engine oil residue stands out as a modifier since it is a high-volume byproduct from the recycling of used oils without much value for further refining. Engine oil typically is formulated with saturated, high molecular weight alkanes with few branches, possessing low volatility, good high-temperature oxidative stability, and low viscosity at cold winter temperatures (2). Nuclear magnetic resonance spectroscopy shows that waste engine oil residue is entirely saturated and is therefore better described as consisting of equal parts saturates and polar (oxidized) saturates rather than aromatics.…”
Section: Descriptions Of the Materials Used Followmentioning
confidence: 99%
“…It has been applied to asphalt for the characterization of chemical composition and aging, for detection of impurities, and for studying polymer modification. Two of the major advantages of FTIR-ATR applied to asphalts, compared with transmittance FTIR, are (a) the spectrum is obtained without solvent and (b) the chemical influence of solvents can be avoided (2). The instrument used to perform the FTIR-ATR was a Nicolet 6700, from Thermo Fisher Scientific.…”
Section: Dynamic Shear Rheometer Test Procedure: Frequency Sweepmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite numerous efforts on performance of asphalt mixtures containing REOB, conclusions reported were inconsistent and sometimes conflicting. Some studies (e.g., 14,16,18) indicate the adverse effect of the addition of REOB on mixture performance, while other research (e.g., [5][6][7]31) showed that mixtures containing REOB have equivalent or better performance as compared with those without REOB. With the increased potential of using REOB with higher recycled asphalt binder usage, there is a pressing need to investigate the effect of REOB and its dosage to various types of mixture performance across a wide range of temperatures.…”
mentioning
confidence: 99%
“…Even though today's asphalt binders meet the required performance grades, some agencies in the United States and Canada are reporting premature durability failures. These durability issues are being linked to the current asphalt binder production methods, as well as the potential use of REOB when the asphalt binder is produced and modified (3)(4)(5)(6). This issue has led to what some believe is the premature banning or limiting of REOB by a number of state agencies in the United States without proper evidence.…”
mentioning
confidence: 99%